2020
DOI: 10.1186/s12884-020-2832-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyoscine n- butylbromide on labor progress: A systematic review

Abstract: Background: The objective of this systematic review and meta-analysis was to assess the effectiveness of hyoscine n-butylbromide in labor progress.Methods: The databases including PubMed, the Cochrane Library, Science-Direct, Scopus and Web of Science were searched for studies published up to December 2019. Articles that published as randomized controlled trials (RCTs), and full-text articles published in English or other languages were included and participants were primi or multigravida women who were in act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…Second, our results showed an insignificant difference between groups in Side effects like confusion and chest pain, but we did not monitor for dry mouth, constipation, urinary retention, reflux and flushing. However, by data analysis from five studies for the effect of HBB on mouth dryness in a previous metanalysis [27] the difference between HBB and controls was insignificant.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Second, our results showed an insignificant difference between groups in Side effects like confusion and chest pain, but we did not monitor for dry mouth, constipation, urinary retention, reflux and flushing. However, by data analysis from five studies for the effect of HBB on mouth dryness in a previous metanalysis [27] the difference between HBB and controls was insignificant.…”
Section: Discussionmentioning
confidence: 87%
“…In a meta-analysis done by Zaynab and colleagues to assess the effectiveness of hyoscine n-butyl bromide in labor progress, analysis of 11 studies involving 1682 participants showed an insignificant difference in the APGAR score at 1 min between HBB and controls (mean difference =-0.04; 95% CI: [− 0.09, 0.01]). Also, the results of seven studies (involving 1453 neonates) showed an insignificant effect of HBB on APGAR score at 5 min after birth (mean difference = − 0.03; 95% CI: [− 0.08, 0.03]) [27].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review including 17 randomized controlled trials (RCTs) on the use of spasmolytics and duration of labor found a statistically significant reduction in the mean duration of the first stage of labor (i.e., the dilation phase) of 74 min [ 25 ]. A systematic review including 20 RCTs and a meta-analysis including 9 RCTs found a reduction in the mean duration of labor of 58 min and 55 min, respectively, when nulliparous women were treated with hyoscine butylbromide [ 29 , 30 ]. To our knowledge, except from 1 study from Saudi Arabia [ 31 ], there are no studies from high-income countries exploring the effect of hyoscine butylbromide on labor duration.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, except from 1 study from Saudi Arabia [ 31 ], there are no studies from high-income countries exploring the effect of hyoscine butylbromide on labor duration. Previous studies have been conducted in India, Pakistan, Iran, Iraq, Turkey, Nigeria, Mexico, Egypt, and Jamaica [ 29 , 30 , 32 ]. We have only found 1 Egyptian study on the effect of hyoscine butylbromide on slow labor [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all natural childbirth will end according to the proper time. In labor whose time is outside normal limits due to prolonged labor, other factors that can affect the length of labor are presentation abnormalities, inadequate contractions, birth canal abnormalities, twin or generally pregnancies, and anemia (1,7).…”
Section: Introductionmentioning
confidence: 99%